2013
DOI: 10.1080/15228959.2013.785881
|View full text |Cite
|
Sign up to set email alerts
|

Do You See the Signs? Evaluating Language, Branding, and Design in a Library Signage Audit

Abstract: Signage represents more than directions or policies; it is informational, promotional, and sets the tone of the environment. To be effective, signage must be consistent, concise, and free of jargon and punitive language. An efficient assessment of signage should include a complete inventory of existing signage, including an analysis of the types of signs, its location, language, and its design. This article outlines the steps involved in a comprehensive signage audit, which along with a literature review, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…This iterative use of the developing methodology presented opportunities to apply, test, and refine the method. By using the worksheet with adaptations across three library types, the researchers found some commonalities, such as a dearth of directional signs and an extreme prevalence of informational signs (also noted by Stempler and Polger, 2013), abundance of signs, and commons issues with signs.…”
Section: Findings Across the Three Iterationsmentioning
confidence: 99%
See 4 more Smart Citations
“…This iterative use of the developing methodology presented opportunities to apply, test, and refine the method. By using the worksheet with adaptations across three library types, the researchers found some commonalities, such as a dearth of directional signs and an extreme prevalence of informational signs (also noted by Stempler and Polger, 2013), abundance of signs, and commons issues with signs.…”
Section: Findings Across the Three Iterationsmentioning
confidence: 99%
“…Also, when they struggle to locate and retrieve materials, they feel increasing confusion, frustration, and lostness (Beecher, 2004). Signage inventories have found poor placement, visibility, and clarity (Eaton et al, 1993); inconsistency in style (Stempler and Polger, 2013); overuse of library jargon (Eaton et al, 1993); negative messages (Stempler and Polger, 2013); and handwritten signs (Eaton et al, 1993;Stempler and Polger, 2013). Schoonover and Kinsley (2014) found that while students were using directories to locate library areas and materials, the majority preferred speaking to a person for assistance and most used a combination of methods to wayfind.…”
Section: Wayfinding Information Systems In Librariesmentioning
confidence: 99%
See 3 more Smart Citations